Validity and Reliability of the Dental Neglect Scale in German - Katharina Marilena Weil; Theresa Marie Weßlau; Laura Agnes Ingrid Magerfleisch; Hannah Tröger; Lisa Irmscher; David Bantel; Clara Theres Meyer-Probst; Katja Petrowski; Hendrik Berth (Dentistry Journal)
Background/Objectives: The Dental Neglect Scale (DNS) is known and used to evaluate and assess adult behaviors and attitudes related to oral self-care and oral-health. In English-speaking countries, the DNS has been used in many studies. At the moment, there is no validated version of the DNS that is available in the German language. The aim of this study is to validate a German version of the DNS to evaluate and assess the oral health and behavior among the German population. Methods: The study population consisted of N = 311 German adults (180 female, 130 male, 1 diverse) aged from 18 to 90 years from a dental clinic in Germany. The participants answered a questionnaire. In addition to questions on their socio-demographic background and the DNS, the survey included more standardized instruments relating to preventive behavior, dental anxiety, and oral health. Results: The DNS was translated into German. An explanatory factor analysis was conducted, which supported the unifactorial structure of the scale. The following results were obtained for the reliability of the resulting DNS: Cronbach’s Alpha = 0.710, McDonald’s Omega = 0.711, and Mean = 25.63 (SD = 4.02, Range 12–30). Convergent and divergent validity were demonstrated through associations between the DNS and various oral health scales, and by differences between genders and age groups. Conclusions: This study confirms the quality of the criteria of the DNS for German adults. The DNS is a convincing instrument that is used for epidemiological studies in the field of dentistry and psychology. Further validation with other samples should be conducted.